THE RELATİONSHİP OF GREEN ADVERTİSİNG ATTİTUDE AND ENVİRONMENTAL AWARENESS İN Z GENERATİON CONSUMERS (Third Sector Social Economic Review, 2023)
Today, the increase in the sensitivity of individuals to environmental problems has been one of the factors that motivate businesses to follow marketing strategies in this direction. Based on this, it is seen that the green advertising activities of the enterprises have become more and more widespread recently. In this regard, it is very important to determine the sensitivity of the young generation to the problems that pose a threat on a global scale. For this purpose, it is aimed to determine the attitudes of the Z generation consumers aged 18 and over, living in Ankara and Sivas, towards green advertising and to reveal the relationship between the attitude shown and environmental sensitivity. In this context, online and face-to-face questionnaires, which were determined as research management, were applied to 301 participants in the study. According to the findings, while there is no significant difference between gender and all sub-dimensions of green advertising attitude, there is a significant difference in terms of gender in all sub-dimensions of environmental sensitivity; It has also been determined that there is a significant difference between all sub-dimensions of consumers' green advertising attitudes and product purchasing. It is desired that the results of the study will guide and contribute to the determination of future strategies of operators, field researchers and marketing managers who see the Z generation as their target audience.
Keywords: Generation Z; Green Advertising; Green Advertising Attitude; Environmental Awareness